2016
DOI: 10.3311/ppci.8210
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prediction of moments in highrise composite frames considering cracking and time-effects

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Jasim and Al-Jabbri discussed the application of artificial neural network in the design of continuous composite beams by the plastic method [ 14 ]. Pendharkar et al used the neural network model to quickly predict the inelastic moment in the high-rise composite frame [ 15 ]. Kalibhat and Upadhyay proposed two different cross section improvers and the proposed simplified numerical program that has advantages in flexibility, versatility, and ease of use [ 16 ].…”
Section: Related Workmentioning
confidence: 99%
“…Jasim and Al-Jabbri discussed the application of artificial neural network in the design of continuous composite beams by the plastic method [ 14 ]. Pendharkar et al used the neural network model to quickly predict the inelastic moment in the high-rise composite frame [ 15 ]. Kalibhat and Upadhyay proposed two different cross section improvers and the proposed simplified numerical program that has advantages in flexibility, versatility, and ease of use [ 16 ].…”
Section: Related Workmentioning
confidence: 99%
“…nd floor of a 72-storey high-rise building for automatic and real-time measurements of the shortening of vertical members to achieve more precise construction. Alternatively, Pendharkar et al [21] developed a neural network model for rapid prediction of the inelastic behavior. Indeed it was reported that the methodology presented in their study could be extended for further rapid prediction of inelastic deflections in high-rise frames in which the effect of axial shortening of the columns is significant.…”
mentioning
confidence: 99%